CAMEL RATIO ON PROFITABILITY BANKING PERFORMANCE (MALAYSIA VERSUS INDONESIA) - Badrul Munir, Maryam binti; Ahmad Bustamam, Ummi Salwa (International Journal of Management, Innovation & Entrepreneurial Research, 2017)
Purpose: This research analyzed about profitability banks performance based on the CAMEL (Capital Adequacy, Asset Quality, Management, Earnings and Liquidity) on the Bank's profitability. Capital adequacy measured by debt equity ratio (DER) and non-performing loans (NPL), asset quality measured by return on assets (ROA), management will be measured by cost per income, earnings measured by return on equity (ROE) and liquidity measured by interest expense and deposit. Methodology: The samples were 114 samples (from 10 bank in Malaysia and 9 bank in Indonesia) since 2010-2015. This analysis used descriptive method and multiple regression analysis, the result of this research indicated that banking profitability have a good performance based on CAMEL analysis. Findings: From the results of regression, the CAMEL analysis has a significant relationship to the bank profitability Practical Implications: The study demonstrated the use of CAMEL analysis to measure bank profitability. If bank performance declining through the CAMEL analysis so the Bank should make a decision to make a better performance changes of banking. Social Implications: This study was about the importance of camel analysis measuring the performance banking. CAMEL analysis detected the decrease in performance in any business sector. Originality/Value: This analysis adapted and adopted the study conducted by Sahut and Mili(2011), but this study focusedonly on the comparative performance between conventional and Islamic banking between Malaysia and Indonesia. Research Limitations/Implications: Comparison of CAMEL analysis focused on two countries between Malaysia and Indonesia (it also involves the comparative analysis of conventional and Islamic bank) to gain the profitabilityof banking, ROI with short period since 2010 until 2015